Making the empire work : labor and United States imperialism - Bender, Daniel E.; Lipman, Jana K. (Culture, labor, history., 2015)
Millions of laborers, from the Philippines to the Caribbean, performed the work of the United States empire. Forging a global economy connecting the tropics to the industrial center, workers harvested sugar, cleaned hotel rooms, provided sexual favors, and filled military ranks. Placing working men and women at the center of the long history of the U.S. empire, these essays offer new stories of empire that intersect with the "grand narratives" of diplomatic affairs at the national and international levels. Missile defense, Cold War showdowns, development politics, military combat, tourism, and.